CHALLENGES OF MANAGEMENT AND CARE IN NORMAL BIRTH CENTERS: QUALITATIVE STUDY WITH OBSTETRIC NURSES - Adriano da Costa Belarmino; Maria Eunice Nogueira Galeno Rodrigues; Patrícia Lima Rodrigues; Luiza Jane Eyre de Souza Vieira; Saiwori de Jesus Silva Bezerra dos Anjos; Antonio Rodrigues Ferreira Júnior (Universidade Federal do Paraná, 2024)
Objective: To understand obstetric nurses' challenges in managing work and care in normal birth centers. Method: A qualitative study was carried out in normal birth centers in Ceará, Brazil. Thirteen nurses and obstetric care coordinators were interviewed between April and July 2020. The thematic categories were organized in Nvivo 12 Pro® software and discussed using the theoretical-philosophical framework of the Sociology of Professions. Results: care practices, such as comfort massages, are carried out in conjunction with elements of work management, such as the sizing of the nursing team. It emerged that there are important skills for acting as autonomy and leadership of the nursing team, but elements such as fragile trust and interaction limit the full development of activities. Final considerations: there are challenges for management and care in normal birth centers, such as consolidating autonomy and building trust with the health team.